Aspek Gramatikal dan Leksikal Lirik Lagu Gala Bunga Matahari Karya Sal Priadi - Nurhaliza, Julia Najma; Wahyono, Hari (UPA Bahasa Universitas Tidar And HISKI Kedu, 2025)
The aim of the research carried out was to analyze the grammatical and lexical structure used in the lyrics of the song